Uma abordagem para minimização de consumo de energia em redes de sensores sem fio com sorvedouros móveis - Carla Oliveira Bechelane (2009)
In this work, we introduce a new network topology model and algorithms to minimize the energy consumption in Wireless Sensor Networks (WSNs) with mobile sinks. On the one hand, the proposed optimization problem explicitly minimizes the energy consumption rates due to message forwarding. On the other hand, it also attempts to keep message delay rates at low levels by imposing a maximum distance to be traveled by each mobile sink. Inaddition to all that, our approach also differs from most studies in the literature since the clustering and routing problems are dealt jointly. To the best of our knowledge, the Combinatorial Optimization Problem that arises when all these features are considered together has never been studied before. We present a Mixed Integer Programming formulation for the problem based on network flows and various heuristics to quickly find feasible integer solutions. Our computational experiments indicated that the proposed heuristics works pretty well in practice. We also implemented a simulation framework which embeds the proposed heuristics to validate the network topology introduced here. The simulation results show that our approach leads to significant improvements for all Quality of Service parameters in WSN like energy consumption, network lifetime, among others.